Zasady porządkujące życie społeczeństwa postindustrialnego dotyczące sektora publicznego - Majewska, Maria (Studia Prawa Publicznego, 2022)
The aim of this article is to identify the main principles for how the public sector functions in a post-industrial society. The research method adopted was a meta-analysis of the results of research by various authors on the issues of managing the development of post-industrial society. The subject of the meta-analysis was primarily literature in the field of knowledge management, development economics and new growth theories. The post-industrial society presented in the article appears as a land of happiness, where everyone works together to multiply the common good, guided by the following principles: knowledge gives access to power because post-industrial society is a meritocracy; social standing depends on diligence and willingness to take advantage of the offers of the educational system; the role of the state is to provide and safeguard open access to the ruling elite for anyone who wishes to learn and improve their conduct by developing objectively formulated, fair and impartial procedures for filling public sector positions. Decision-makers, i.e. those who have power, are not only professionals but also people who put the common good before self-interest. Representatives of the science sector set the directions of state policy and prepare strategies for achieving them. The science sector is independent of government and business, which is manifested in the freedom of to teach and conduct research. Social inequalities are being tackled and citizens can monitor the spending of public funds, since we are dealing with a welfare state. The prevailing political system is participatory democracy. Citizens participate in the life of society on an equal footing, and decisions about the future of society are consulted with them. Political decentralization in the management of public administration is common.